(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The study aims to investigate the assessment of groundwater quality and its suitability for agricultural use in the Al-Shirqat area in Salahaldin Governorate. The selected (23) wells are distributed over the study area at two different locations. The first location includes 12 wells and is located within the sedimentary soil unit, while the second site includes 11 wells and is located within the calcareous soil unit. Well water samples are analyzed to measure the positive and negative dissolved ions (Ca, Mg, Na, K, HCO3, Cl, and SO4). The irrigation water quality criteria (SAR, Na% %, ESP, PS, Mg% % and TDS) are calculated, and spatial distribution maps are prepared. The results show that the concentrations of calcium and chloride ions exceed the permissible limits needed for irrigation, while the concentration of sodium ions is within the permissible limits according to FAO standards. The values of EC range between 3-10 dSm-1 and a low exchangeable sodium absorption ratio SAR (less than 4.48) under the S1C4 group.